Effective leadership and the organizational climate in the educational institutions of the district from Victoria-Lima - Gálvez Suárez, Eric Dalmacio (2018)
The research, entitled Effective leadership and organizational climate in the educational institutions of the district of La Victoria-Lima, aimed to determine the relationship of effective leadership with the organizational climate of educational institutions in the district of La Victoria-Lima. The hypothetical deductive method was used, based on a non-experimental, cross-section quantitative design approach. The technique used was the survey and the instrument the questionnaire, which was applied to a non-probabilistic sample of 144 teachers of initial, primary and secondary. The results allowed to determine the significant correlation, with a significance of 0.644*.